DYNAMICS OF MICRONUTRIENTS IN ARABLE SOILS: IMPLICATIONS FOR SUSTAINABLE AGRICULTURE - Bakare, A.O.; Efenudu, I.U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study investigated the dynamics of micronutrients (Fe, Zn, Cr, Cu, and Mn) in arable soils under yam and cassava cultivation in Nigeria. Soil samples were collected from two separate farms at four depths (0-30, 30-60, 60-90, and 90-120 cm) and analyzed for physical and chemical properties, including micronutrient content. The results showed that topsoil (0-30 cm) had the highest micronutrient content, with mean values of 354.0 mg/kg (Fe), 117.0 mg/kg (Mn), 13.1 mg/kg (Zn), and 52.66 mg/kg (Cu) in yam farms, and 368.0 mg/kg (Fe), 118.4 mg/kg (Mn), 13.55 mg/kg (Zn), and 61.24 mg/kg (Cu) in cassava farms respectively. The micronutrient content decreased with increasing soil depth, with significant correlations between soil physical and chemical properties (pH, sand content, organic carbon). The study highlights the importance of integrated soil fertility management practices that account for micronutrient variability with depth and crop type. The findings have significant implications for sustainable agriculture, emphasizing the need for targeted soil management practices to mitigate micronutrient deficiencies and promote ecosystem services in arable soils. Regular soil testing and nutrient management planning are crucial to ensure crop nutrient requirements are met without depleting soil nutrient reserves.